Nutritional status of under five children attending Anganwadi in rural area of central India - Khobragade, Ashish Wasudeo; Yadav, Rajendra Govardhan (International Journal Of Community Medicine And Public Health, 2020)
Background: Under five mortality rate (U5MR) of India is 36. Malnutrition is most important factor contributing to under five mortality. Methods: 354 children in the age group 0-5 years were included in the study. Weight, height and Mid Upper arm circumference was measured. Data was analyzed by using ‘Anthro’ software. Z scores were calculated. Prevalence of stunting, wasting and underweight was calculated. Results: Prevalence of stunting, wasting and underweight is 35%, 6.4% and 15.8% respectively. Conclusions: Malnutrition is statistically associated with socioeconomic status, maternal literacy and exclusive breast feeding.